Process Indicators for Grading Group Essays: Learning Analytics of Assessment Data and Online Behaviour - Mei-Shiu Chiu; Ya Ping (Amy) (Athens Institute for Education and Research, 2023)
The aim of this study was to identify process-related indicators for grading group essays. The research participants were students registered in a teacher-training course using an instructional design with face-to-face and digital blended learning. The course required the students in small collaborative groups to design, implement, and evaluate a teaching program using creative pedagogical designs, which were documented using group essays. Four indicators relating to group essays along the course process were collected: (A) group essay grades assessed by different agents, (B) students' other course grades or behaviours (i.e., multiple assessments) as well as (C) comment behaviours and (D) version history behaviours through an online co-editing system (i.e., Google Docs). Statistical analysis results indicated that the instructor's group essay grades were related to the group essay grades assessed by out-group peers (i.e. peers from other groups), online group comment frequencies, and online group comment interaction density.